MLC tracking for lung SABR is feasible, efficient and delivers high-precision target dose and lower normal tissue dose. (February 2021) - Booth, Jeremy; Caillet, Vincent; Briggs, Adam; Hardcastle, Nicholas; Angelis, Georgios; Jayamanne, Dasantha; Shepherd, Meegan; Podreka, Alexander; Szymura, Kathryn; Nguyen, Doan Trang; Poulsen, Per; O'Brien, Ricky; et al.
Highlights: MLC tracking was shown to be safely and efficiently delivered for lung SABR on a standard linac. Statistically significant reductions in PTV, mean lung dose and lung V20Gy compared to ITV-based. Variation between delivered and planned dose was reduced with MLC tracking. Abstract: Background and purpose: The purpose of this work is to present the clinical experience from the first-in-human trial of real-time tumor targeting via MLC tracking for stereotactic ablative body radiotherapy (SABR) of lung lesions. Methods and materials: Seventeen patients with stage 1 non-small cell lung cancer (NSCLC) or lung metastases were included in a study of electromagnetic transponder–guided MLC tracking for SABR (NCT02514512). Patients had electromagnetic transponders inserted near the tumor. An MLC tracking SABR plan was generated with planning target volume (PTV) expanded 5 mm from the end-exhale gross tumor volume (GTV). A clinically approved comparator plan was generated with PTV expanded 5 mm from a 4DCT-derived internal target volume (ITV). Treatment was delivered using a standard linear accelerator to continuously adapt the MLC based on transponder motion. Treated volumes and reconstructed delivered dose were compared between MLC tracking and comparator ITV-based treatment. Results: All seventeen patients were successfully treated with MLC tracking (70 successful fractions). MLC tracking treatment delivery time averaged 8 minutes. The time from the start of CBCT to the end of treatment averaged 22 minutes. The MLC tracking PTV for 16/17 patients was smaller than the ITV-based PTV (range −1.6% to 44% reduction, or −0.6 to 18 cc). Reductions in mean lung dose (27 cGy) and V20Gy (50 cc) were statistically significant ( p < 0.02). Reconstruction of treatment doses confirmed a statistically significant improvement in delivered GTV D98% ( p < 0.05) from planned dose compared with the ITV-based plans. Conclusion: The first treatments with lung MLC tracking have been successfully performed in seventeen SABR patients. MLC tracking for lung SABR is feasible, efficient and delivers high-precision target dose and lower normal tissue dose.